Solvent exposure and respiratory health status among workers in a tire retreading factory - Yazin, Nik Khairol Reza Md (2006)
Introduction: Rubber industry is known to have abundant chemicals, mainly solvents, in their working environment. Although the effects of these substances on respiratory health are well known, there is limited local information. This study was aimed to explore the respiratory health status among workers, solvent exposure in the workplace, level of KAP, and associated factors, which potentially impair the lung function among workers in a tire retreading factory. Methods: In this cross sectional study, questionnaires were distributed to available 95 male production workers to obtain sociodemography, personal and work related information, respiratory symptoms and KAP. Physical examination and lung function test were conducted. Area samplings were done for toluene, benzene and xylene, followed by personal air sampling and urine sampling for toluene. Toluene was selected to be checked because toluene level was highest in area sampling. Result: All participants were Malay with mean (SD) age of 36.6 (6.29) years and median (IQR) working duration was 133.8 (63.53) months. Chest tightness (32.6%) was the commonest symptom followed by phlegm production (27.4%), morning cough (10.5%) and shortness of breath (10.5%). Physical examination revealed normal findings whereas mean (SD) of FVC, FEVt, FEVtiFVC ratio and FEF2s-1s%, were 3.6 (0.56) litre, 2.9 (0.45) litre, 80.4 (7.82) percents and 3.5 (1.52) litre/second, respectively. Known associated factors for lung function such as age, height and weight, and occupational factors such as exposure to dust and work shift were noted to be significantly associated with at least one parameter of lung functions. In KAP assessment, prevalence for bothknowledge level below 80 percent score were 45.3% and 21.1 %, whereas prevalence for attitude level below 70 percent score was 25.3% and prevalence for practice level below 80% score was 89 .5%. In environmental sampling, toluene level was ranged from undetectable to 300 ppm, level of personal sampling ranged from undetectable to 5.5 mg/m3 and range of urine hippuric level was from 0.02 to 3.63 with median (IQR) of0.26 (0.40) gig creatinine. Conclusion: The study demonstrated an evidence of toluene exposure and mild effect on respiratory health among workers. It also revealed the needs for intervention in order to improve KAP in this workplace.